Don't Wage War in the Media, or Be Silent and Forfeit It All! - S D. Cummings (International Society of Explosives Engineers, 1995)
"CRACKS CONCERN CORPORATION" Was the headline on the front page of the Terre Haute Tribune Star, March 1994. Having spent several years following up on blast-induced damage allegations made this article especially interesting. Knowing that there were no operating mines within 30 miles of this newly built, yet to be occupied building, also made the reading more enjoyable. The article went on to read, "Vigo County school officials have asked architects to find out whether some cracks in walls at the new school are due to NORMAL settling or if they indicate serious structural problems." It is obvious that if there were a mine within "Feeling" distance, blasting and the operator would have immediately become suspect as at least one of the potential causes. More alarming is that the investigation may have stopped there.